ANALISIS HUBUNGAN SISTEM TRANSIVITAS DAN KONTEKS SITUASI DALAM PIDATO POLITIK HATTA RAJASA: TINJAUAN SISTEMIK FUNGSIONAL - Nurfaedah Nurfaedah (Universitas Negeri Makassar, 2017)
Abstract. The Analysis Relation of Trasivity System and Situation Context in Hatta Rajasa’s Political Speech: Systemic Functional Linguistics Overview. The research aims to describe relation of the type of transitivity process and situation context in Hatta Rajasa’s Political Speech.This research is a descriptive research, used a qualitative approach and was supported by quantitative data. The object of research is in the form of political speech text delivered by Hatta Rajasa. The data sources used are the spoken data in the form of audiovisual. The population is in the form of political speech text delivered by Hatta Rajasa. The research’s samples are the process type, the participants, and the circumstances found in the data. The method used is the method of seeing, then proceed with the noted technique. The research finding indicated that (1) the type of process which was found in the analysis of Hatta Rajasa’s political speech consists of six process that are the material process, the mental process, the relational process, the behavioral process, the verbal process, and the existential process. The dominated process is the material process that was represented the life that was oriented on the action, the activity, and the real action (2). the circumstances found were the location, manner, cause, accompanying, and ranges. There was a dominating percentage in appearance and there were only appear occasionally. The most frequent circumstance is the location circumstance that indicated a desire of the speaker to do something through the specified time and place planning. (3) based on the analysis of situational context connected with the analysis of transitivity system can be known the purpose of the delivery of Hatta Rajasa’s political speeches through the process, the participant, and the circumstances. It can be seen that Hatta Rajasa’s desire is the intention of delivering the ideas on the realization of the ideals of the Indonesian people through the developing of a democratic and economic system